Health on equal terms? Västra Götaland, 2012 - Health on equal terms, Västra Götaland - 2012 - Public Health Agency of Sweden (City of Gothenburg, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2012, the City of Gothenburg ordered an additional sample for Gothenburg.

The additional sample in 2012 included all individuals aged 16-84 years living in Gothenburg and consisted of 3,050 individuals. The total sample of Gothenburg, including the national sample, was 4,149 individuals. The questionnaire was answered by 1,801 individuals from Gothenburg, representing a response rate of 43,5 percent.

Including the national sample produced by Statistics Sweden (SCB), a total of 2,971 individuals participated from Västra Götaland County.

The questionnaire was printed in two versions. Addition to the national public health questionnaire, a similar questionnaire was conducted for the sample in Gothenburg including some extra questions. The national questionnaire consisted a total of 144 questions and the questionnaire for the sample in Gothenburg consisted a total of 189 questions. Both questionnaires covered issues of health, lifestyle, economic conditions, work and employment, and security and social relations.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Gothenburg was to investigate the health in the population living in Gothenburg.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2012 beställde Göteborgs Stad ett tilläggsurval för Göteborg.

Tilläggsurvalet för 2012 års undersökning inkluderade invånare 16-84 år i Göteborgs Stad, och bestod av 3 050 personer. Det totala antalet urvalspersoner, dvs. tilläggsurvalet samt urvalspersoner från Göteborgs Stad i det nationella urvalet, var 4 149 personer. Frågeformuläret besvarades av totalt 1801 personer i urvalet, vilket motsvarade en svarsfrekvens på 43,5 procent.

Antal svar för hela Västra Götalands län, d.v.s inklusive det nationella urvalet som tagits fram av Statistiska Centralbyrån (SCB), uppgick till totalt 2971 individer.

Statens folkhälsoinstitut utformade frågorna i den nationella frågeblanketten i samarbete med SCB. Göteborgs Stad utformade ett antal tilläggsfrågor tillsammans med landstingen i Örebro, Sörmland, Uppsala och Västmanland. Den nationella blanketten bestod av 84 numrerade frågor. Flera av dem hade delfrågor, vilket genererade totalt 144 frågor. Blanketten med tilläggsfrågor bestod av exakt samma frågor som den nationella blanketten samt ytterligare 20 numrerade frågor (totalt 45 frågor inklusive delfrågor). Frågorna handlade bland annat om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Göteborgs Stad var att ta reda på hur befolkningen i Göteborgs Stad mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2012 - Hälsa på lika villkor, Västra Götaland - 2012
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende